Contribution of lower extremity muscles to center of mass acceleration during walking: Effect of body weight. (January 2023) - Kim, Hyun Kyung; Lu, Shiuan-Huei; Lu, Tung-Wu; Chou, Li-Shan
Abstract: Overweight or obesity is known to be associated with altered activations of lower extremity muscles. Such changes in muscular function may lead to the development of mobility impairments or joint diseases. However, little is known about how individual lower extremity muscles contribute to the whole-body center of mass (COM) control during walking and the effect of body weight. This study examined the contribution of individual lower extremity muscle force to the COM accelerations during walking in overweight and non-overweight individuals. Musculoskeletal simulations were performed for the stance phase of walking with data collected from 11 overweight and 13 non-overweight adults to estimate lower extremity muscle forces and their contributions to the COM acceleration. Mean time-series data from each parameter were compared between body size groups using Statistical Parametric Mapping. Compared to the non-overweight group, the overweight group revealed a greater gastrocnemius contribution to the mediolateral ( p  = 0.006) and vertical ( p  < 0.001) COM accelerations during mid-stance, and had a lower vastus contribution to the anteroposterior COM acceleration ( p  < 0.001) during pre-swing. Increased contributions from the large posterior calf muscles to the mediolateral COM acceleration may be related to efforts to alleviate COM sway in overweight individuals.